Pengaruh Persepsi Harga dan Kualitas Pelayanan Terhadap Keputusan Penumpang Pengguna Maskapai Citilink di Bandar Udara Internasional Ahmad Yani Semarang - Hamelltha Dhasya; Fryda Fatmayati (Jurnal Multidisiplin Madani, 2022)
Air transportation facilities can not be separated from the existence of technological advances from the results of human thought as an effort to provide better, safe and comfortable transportation services. Likewise with prices, people in Indonesia are currently very considerate of prices. Because the price and quality of service is one of the factors supporting the decision of passengers in choosing an airline. One of the airlines operating in Indonesia is Citilink. This study aims to determine and explain the effect of price perceptions and service quality on the decisions of passengers using Citilink airlines at Ahmad Yani International Airport, Semarang. This study uses a quantitative approach by distributing questionnaires to 100 respondents taken from the population of Citilink airline users who have flown from Ahmad Yani International Airport, Semarang. From the results of the study, it was found that the variation in passenger decisions was 63.6%.